2019
DOI: 10.1055/s-0039-1700883
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Cytoreduction and HITOC for Thymic Malignancies with Pleural Dissemination

Abstract: Background Objective of this study was to assess postoperative morbidity and mortality as well as recurrence-free and overall survival in patients with thymic malignancies and pleural dissemination undergoing surgical cytoreduction and hyperthermic intrathoracic chemotherapy (HITOC). Methods Retrospective study between September 2008 and December 2017 with follow-up analysis in May 2018. Results A total of 29 patients (male: n = 17) with thymic malignancies and pleural spread (primary stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The cohorts range from case series with four patients to a maximum of 104 patients (20,24). The survival (30,31,37). With treatment concepts including only surgery and radiochemotherapy reported 5-year survival rates are between 53% and 88% (38,39).…”
Section: Clinical Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The cohorts range from case series with four patients to a maximum of 104 patients (20,24). The survival (30,31,37). With treatment concepts including only surgery and radiochemotherapy reported 5-year survival rates are between 53% and 88% (38,39).…”
Section: Clinical Datamentioning
confidence: 99%
“…With treatment concepts including only surgery and radiochemotherapy reported 5-year survival rates are between 53% and 88% (38,39). When combined with HITHOC, 5-year survival rates of 80-92% were demonstrated (26,28,30,37). Survival in these studies has depended especially on tumor histology since thymic carcinoma showed a considerably worse survival and therefore should be treated and reported as a separate entity (30,37).…”
Section: Clinical Datamentioning
confidence: 99%
See 2 more Smart Citations
“…2 With the application of the HITOC after macroscopic complete pleural tumour resection, it is expected to obtain better local tumour control, and thereby improve progression-free as well as overall survival. [2][3][4] The few existing case series or single-centre retrospective studies in patients with MPM and thymic tumours have shown some encouraging results in this regard. 2 5-9 However, a prospective study showing an advantage in survival does not yet exist.…”
Section: Introductionmentioning
confidence: 99%